2008
DOI: 10.1161/atvbaha.107.149146
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombotic Effects of Fibronectin Isoforms Containing the EDA Domain

Abstract: Objective-Fibronectin (FN) plays an important role in the formation of stable arterial thrombi at the site of vascular injury.FN containing Extra Domain A (EDA ϩ FN) is absent from normal plasma, but elevated plasma levels of EDA ϩ FN are found in several pathological conditions. We hypothesized that EDA ϩ FN plays a special role in thrombosis. Methods and Results-We used mouse strains constitutively including (EDA ϩ/ϩ ) or excluding (EDA Ϫ/Ϫ ) the EDA domain in all tissues and plasma. Using a flow chamber and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
50
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 37 publications
3
50
0
Order By: Relevance
“…Platelets from adult donor mice were prepared as described 25,26 and briefly explained in the supplemental Methods on the Blood Web site. Intravital microscopy was performed as described.…”
Section: Visualization Of Platelet Adhesion and Thrombus Using Intravmentioning
confidence: 99%
See 1 more Smart Citation
“…Platelets from adult donor mice were prepared as described 25,26 and briefly explained in the supplemental Methods on the Blood Web site. Intravital microscopy was performed as described.…”
Section: Visualization Of Platelet Adhesion and Thrombus Using Intravmentioning
confidence: 99%
“…Intravital microscopy was performed as described. 25,26 Platelets labeled with fluorescent calcein green, acetoxymethyl (AM) esters (1.25 3 10 9 platelets/kg) or fluorescent calcein red-orange, AM were infused through the retro-orbital plexus in mice anesthetized with 100 mg/kg ketamine and 10 mg/kg xylazine. An incision was made through the abdominal wall to expose the mesentery, and the arterioles of diameter (approximately 100-150 mm) were studied.…”
Section: Visualization Of Platelet Adhesion and Thrombus Using Intravmentioning
confidence: 99%
“…9 In pathological disease states such as diabetes and ischemic stroke, plasma levels of cellular Fn containing extra domain A (Fn-EDA1) can become elevated. 13,14 Previously, it was shown that inclusion of the EDA segment gives Fn a prothrombotic potential in vivo 15 ; however, the underlying mechanisms of this effect still remain unknown. The EDA segment of cFn, but not other domains, has been shown to activate human Toll-like-receptor (TLR) 4 expressed in HEK293 cells.…”
Section: Introductionmentioning
confidence: 99%
“…10 Although its function is not well understood, FN EIIIA has been previously linked to a variety of in vitro cellular events and in vivo molecular outcomes. Increased expression of EIIIA+ isoform modulates cell cycle progression, myofibroblast differentiation, 11 prothrombotic effects on platelets, 12 and protection of vessel walls in conditions of disturbed flow.…”
mentioning
confidence: 99%